PENGELOLAAN STRES PADA GURU HONORER DALAM KONTEKS PENDIDIKAN: KAJIAN LITERATUR - Yadi Suryadi; Aslan (CV. Adiba Aisha Amira, 2025)
Honorary teachers often face various challenges that can potentially trigger stress, such as low job status, career uncertainty, and unbalanced workloads. The stress experienced by honorary teachers can have a negative impact on teaching quality, mental health, and social relationships. This article aims to examine effective stress management strategies for honorary teachers in the context of education based on a literature review. The results of the study indicate that internal approaches such as mindfulness, relaxation techniques, and coping skills, combined with external support in the form of psychological counselling, stress management training, and supportive institutional policies, can help honorary teachers manage work pressure more effectively. In conclusion, holistic stress management, which involves individual, social, and systemic aspects, is essential for improving the well-being of honorary teachers while supporting better quality education.